Multiparasitism by myxozoans in Pygocentrus nattereri (Characiformes: Serrasalmidae) from Sacaizal Lake, in the municipality of Pracuúba, state of Amapá, Brazil - Nayana Moraes de Sena; Jhonata Eduard; Camila Maria Barbosa Pereira; José Ledamir Sindeaux Neto; Michele Velasco (Revista Brasileira de Parasitologia Veterinária)
Abstract The present study described the morphological characteristics of myxospores of cnidarians belonging to the class Myxozoa at different infection sites in Pygocentrus nattereri Kner 1858 (Characiformes: Serrasalmidae), found in Lake Sacaizal, in the municipality of Pracuúba, state of Amapá, Brazil. In 44% of the specimens analyzed, myxospore gill filaments of the genus Henneguya were observed with a pyriform sporal body, presenting long caudal projections internally, with two polar capsules. In some filaments, branchial arches, and fin cysts (with a prevalence of 22%) pyriform Myxobolus myxospores were observed, which were larger than those found in the caudal kidneys, where the myxospores had an elliptical shape, demonstrating the presence of two morphotypes in the same host. Thus, these morphological data contribute to the diversity of myxozoans in Amazonian fish, particularly P. nattereri in their natural environment, with the first occurrence of these parasite genera in this host.